Ancient aliens. Season 09 [videorecording (DVD)] - Clotworthy, Robert, 1955- (A&E Television Networks, 2016)
Pyramids hidden beneath the ice of Antarctica. Egyptian hieroglyphs of flying ships carved on sandstone walls in Australia. Giant Caucasian mummies buried beneath the desert in China. A new planet found right in our own solar system. According to ancient astronaut theorists, these discoveries may reveal not only that extraterrestrials visited Earth in the distant past, but that they may still be among us today. In season nine, the search for answers strikes out into uncharted territory.